(untitled) (Al-Academy, 2016)
running the requirement color important place in object of life activity both public and private, Fallon makes represents energy expressive and aesthetic in designing furniture street, especially (positions waiting buses passenger transport)which took looms large in attention receiver designer also, through civilized development and urban and change the city. Requirement, The positions of waiting progress jobs service and that would interact to produces Photos aesthetic Furniture for space street and understand receiver, affect the operation his life and the development of his environment and his psyche and culture of because they entity variable and sophisticated, impose on us to find foundations a design and conditions of chromatic especially dealing with the positions of the wait, thus be reflected on novelty design performed in the street, And reviews the searching through separated first problem of the research a major focus includes a by requiring chromatography and functional performance and aesthetic and its relationship to a time waiting, as well as effectiveness of means design and connotations artistic and cultural and their impact on aspects psychological and physiological with the recipient, without feeling like by a factor boredom and turmoil induced from the waiting, and for that discussed a chapter second reviewed the tract the historical development of positions wait, and the relationship between them and the vocabulary of furniture the street in addition to addressing most important raw materials used in the design and how to achieve the requirement of chromatography as well as the identify the jobs form into the field design, also the potential constructivist for Design according styles technical regulation for the colors and its association perception sensuous and cognitive the receiver , down to a set of results adopted the designer principle sorting the color through distributing trends of fonts Handaseya (rectus, the curved) to accentuate design elements falling within the the scene optical and use techniques of antagonism the values colorimetric to lure the recipient, and enhance the designs into multiple requirements for in Gadgets expressive color (the lighting industrialized- substitutes to nonpainted ores materials such as aluminum, glass, wood) and adopt the the designer to metaphors Bashoa_khas the the environment civilizational of heritage and icons in Iraq to building a formality order.